ANALYSIS OF DIGITAL MARKETING COMMUNICATION STRATEGIES OF TASGROSIRSEDERHANA IN INFLUENCING CONSUMER BEHAVIOR ON THE SHOPEE PLATFORM - Rofi, Muhammad Hafiz Ainur; Hariyanto, Didik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The rapid digital transformation encourages MSME players to adopt effective marketing communication strategies in order to be able to compete on e-commerce platforms. Tasgrosirsederhana is one of the MSMEs engaged in women's fashion products, especially the sale of bags, which has been operating on the Shopee platform since 2020. Based in Pasuruan Regency, East Java, this store has managed to reach the national market with more than 550 thousand followers and product sales every month. The purpose of this study is to examine how the digital marketing communication strategy applied by Tasgrosirsederhana is able to shape consumer behavior based on the theory of the hierarchy of effects approach of Robert J. Lavidge and Gary A. Steiner. Method: This study uses a descriptive qualitative method with data collection techniques in the form of direct observation, digital documentation, and in-depth interviews with store managers and active consumers. Result: The results of the study show that digital marketing strategies have successfully steered consumers through the six stages of the effect hierarchy model. Namely: increasing awareness through paid advertising, conveying knowledge through detailed and attractive product information, forming liking through affordable prices and responsive services, strengthening preferences through promotions and positive reviews, building conviction through live streaming and testimonials, and encouraging purchases through a satisfying shopping experience. Novelty: This overall strategy shows that planned and structured digital marketing communication can be the main strength of MSMEs in increasing competitiveness in the digital.